Varenicline and related interventions on smoking cessation: A systematic review and network meta-analysis. (1st December 2022) - Guo, Kangle; Zhou, Liying; Shang, Xue; Yang, Chaoqun; E, Fenfen; Wang, Yan; Xu, Meng; Wu, Yanan; Li, Yanfei; Li, Meixuan; Yang, Kehu; Li, Xiuxia
Abstract: Background: Based on randomized controlled trials, a network meta-analysis was conducted to compare treatment effects across varenicline and related smoking interventions. Methods: English databases were screened for randomized controlled trials reporting the effect of varenicline as treatment for smoking. The risk of bias in included trials was assessed using the Cochrane Handbook tool. Stata 15.1 software was used to perform network meta-analysis, and the GRADE approach was used to assess the evidence credibility on the tobacco treatment effects of different interventions. Results: Thirty-four studies involving 26, 130 smokers were included in the network meta-analysis. Varenicline and 11 other interventions were reported, yielding 66 pairs of comparisons. Network meta-analysis showed that varenicline monotherapy or its combination with other interventions were superior in achieving smoking cessation compared to bupropion, nicotine replacement therapy, counselling, and placebo. Furthermore, compared to the varenicline, evident abstinence superiority was found in varenicline + bupropion (odds ratio = 1.49, 95% confidence interval [1.02, 2.18]). Finally, the surface under the cumulative ranking curve value indicated that varenicline + bupropion has the highest probability to become the best intervention. Conclusions: Varenicline monotherapy increased the odds of smoking cessation further than bupropion monotherapy, nicotine replacement therapy, counselling, and placebo, while varenicline combined with other interventions may even achieve a better abstinence effect. More credible evidence has been reported indicating that the combination of varenicline and bupropion is a superior treatment for smoking. Highlights: This network meta-analysis review includes 34 randomized trials of 26, 130 smokers. Among monotherapies, varenicline is highly effective as treatment for smoking. Varenicline combined with other interventions achieves a better abstinence effect. The varenicline + bupropion combination achieves the best effect.